Inhibition of thrombin generation 12 hours after intake of direct oral anticoagulants. Issue 4 (23rd April 2020) - Metze, Michael; Pfrepper, Christian; Klöter, Tristan; Stöbe, Stephan; Siegemund, Roland; Siegemund, Thomas; Edel, Elvira; Laufs, Ulrich; Petros, Sirak
Abstract: Background: The residual antithrombotic activity 12 hours after intake of direct oral anticoagulants (DOACs) is of clinical relevance in the setting of bleeding or urgent surgery. Objective: To evaluate the effects of DOACs on thrombin generation 12 hours after DOAC intake in comparison to baseline and a healthy control group. Methods: Eighty patients were recruited, 20 patients for each approved DOAC: apixaban, edoxaban, rivaroxaban, and dabigatran. The patients were either to be put on anticoagulation for the first time or had stopped taking oral anticoagulation for at least 48 hours. Blood plasma was sampled before (baseline) and 12 hours after starting DOAC for quantification of drug levels and thrombin generation assayed using an automated system (ST Genesia). Sixty‐one blood donors served as control group. Results: The factor Xa inhibitors significantly increased lag time (137%‐219%) and reduced thrombin peak (47%‐76%) and velocity index (17%‐44%) after 12 hours compared to baseline. Dabigatran showed prolongation of lag time to 133% and time to peak to 119%. All patients had residual antithrombotic activity, with reduced thrombin generation parameters 12 hours after DOAC intake compared to baseline and to the healthy control group. This effect remained significant in patients with low residual DOAC plasma levels <50 ng/mL. Conclusion: Thrombin generation remains reduced 12 hours after DOAC intake. While thrombin peak is particularly modified by factor Xa inhibitors, all DOACs prolong the lag time and time to thrombin peak. In the setting of bleeding or urgent surgery, the automated thrombin generation assay may assist in decision making and antidote administration.